Southeast Asian warfare, 1300-1900 - Charney, Michael W. (Handbuch der Orientalistik. Südostasien ;, 2004)
This study offers a comprehensive look at warfare -- its meaning, culture, technology, tactics, and organization -- in an area of the world previously neglected by military historians.